Investigating the Effects of E-Learning as a Method of Curriculum Dissemination for Rural TVET College Students - Makhosi P. Madimabe; Bunmi I. Omodan (Research in Social Sciences and Technology- OpenED Network, 2021)
The study investigates the effects of e-learning as an alternative form of curriculum dissemination for rural Technical and Vocational Education and Training (TVET) college students. This study adopted connectivism theory, which enabled lecturers to reflect and adapt to how learning has changed and the accompanying implications of designing the spaces and structures to the current mode of learning. The researcher made use of two research methods to gather data; phone interviews and questionnaires. The data was analyzed using thematic analysis and the Statistical Package for Social Sciences (SPSS) Version 20.0, Office Word format. The results indicated that the unavailability of technological resources, lack of financial support from single parents’ side due to socio-economic factors, and child-headed families hinder the correct implementation of e-learning and make it difficult to reach its objectives.